Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine the intercepts of the line given by the equation [tex]\( y = 6x + 13 \)[/tex], we need to find both the [tex]\( x \)[/tex]-intercept and the [tex]\( y \)[/tex]-intercept.
### Finding the Y-Intercept:
The [tex]\( y \)[/tex]-intercept is the point where the line crosses the [tex]\( y \)[/tex]-axis. This occurs where [tex]\( x \)[/tex] is zero.
1. Substitute [tex]\( x = 0 \)[/tex] into the equation.
[tex]\[ y = 6(0) + 13 \][/tex]
2. Simplify the equation.
[tex]\[ y = 13 \][/tex]
Therefore, the [tex]\( y \)[/tex]-intercept is the point:
[tex]\[ (0, 13) \][/tex]
### Finding the X-Intercept:
The [tex]\( x \)[/tex]-intercept is the point where the line crosses the [tex]\( x \)[/tex]-axis. This occurs where [tex]\( y \)[/tex] is zero.
1. Set [tex]\( y = 0 \)[/tex] in the equation:
[tex]\[ 0 = 6x + 13 \][/tex]
2. Solve for [tex]\( x \)[/tex]:
[tex]\[ 0 = 6x + 13 \implies 6x = -13 \implies x = \frac{-13}{6} \][/tex]
Therefore, the [tex]\( x \)[/tex]-intercept is the point:
[tex]\[ \left(-\frac{13}{6}, 0\right) \][/tex]
### Summary
- The [tex]\( x \)[/tex]-intercept is [tex]\(\left(-\frac{13}{6}, 0\right)\)[/tex].
- The [tex]\( y \)[/tex]-intercept is [tex]\((0, 13)\)[/tex].
### Finding the Y-Intercept:
The [tex]\( y \)[/tex]-intercept is the point where the line crosses the [tex]\( y \)[/tex]-axis. This occurs where [tex]\( x \)[/tex] is zero.
1. Substitute [tex]\( x = 0 \)[/tex] into the equation.
[tex]\[ y = 6(0) + 13 \][/tex]
2. Simplify the equation.
[tex]\[ y = 13 \][/tex]
Therefore, the [tex]\( y \)[/tex]-intercept is the point:
[tex]\[ (0, 13) \][/tex]
### Finding the X-Intercept:
The [tex]\( x \)[/tex]-intercept is the point where the line crosses the [tex]\( x \)[/tex]-axis. This occurs where [tex]\( y \)[/tex] is zero.
1. Set [tex]\( y = 0 \)[/tex] in the equation:
[tex]\[ 0 = 6x + 13 \][/tex]
2. Solve for [tex]\( x \)[/tex]:
[tex]\[ 0 = 6x + 13 \implies 6x = -13 \implies x = \frac{-13}{6} \][/tex]
Therefore, the [tex]\( x \)[/tex]-intercept is the point:
[tex]\[ \left(-\frac{13}{6}, 0\right) \][/tex]
### Summary
- The [tex]\( x \)[/tex]-intercept is [tex]\(\left(-\frac{13}{6}, 0\right)\)[/tex].
- The [tex]\( y \)[/tex]-intercept is [tex]\((0, 13)\)[/tex].
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.